Budaya Suku Laut Kepulauan Riau di Ambang Perubahan: Tantangan dan Harapan - Annisa Maulidina Haqi; Lina Puryanti; Edi Dwi Riyanto (Jurnal Ilmu Sosial dan Humaniora, 2025)
The Riau Archipelago, rich in marine biodiversity and cultural heritage, has long been home to the Orang Suku Laut, a nomadic maritime community deeply connected to their aquatic environment. This study explores the cultural transformations experienced by the Orang Suku Laut amid rapid modernization and industrialization, with particular attention to their traditional practices, environmental challenges, and strategies for resilience. Employing a qualitative approach grounded in cultural ecology theory, this research draws on extensive library-based data—including peer-reviewed journals, government reports, and ethnographic studies—to analyze the socio-cultural and ecological impacts of development on this indigenous community. Through thematic content analysis, the study reveals significant disruptions to cultural practices, reduced access to marine resources, and identity struggles in the face of urbanization. Nevertheless, the findings highlight opportunities for resilience through community-led heritage preservation, eco-tourism, and adaptive integration into modern governance. This study argues for development policies that uphold indigenous cultural integrity while promoting inclusive sustainability in maritime regions.